Enhanced Visible‐Light Photoactivities of Perovskite‐Type LaFeO3 Nanocrystals by Simultaneously Doping Er3+ and Coupling MgO for CO2 Reduction. Issue 2 (14th November 2019) - Li, Sijia; Li, Yanzhen; Chen, Yajie; Xu, Linna; Chen, Qiuyu; Qu, Yang; Wang, Guofeng; Zhu, Peifen; Wang, Dingsheng; Qin, Weiping
Abstract: The use of solar energy to convert CO2 into chemical fuels not only can create renewable energy but also can alleviate the greenhouse effect. In this work, MgO/LaFeO3  : Er 3+ composites were prepared, and their photocatalytic CO2 reduction capability was tested under visible‐light irradiation. The MgO/LaFeO3  : Er 3+ composites displayed improved charge carrier separation efficiency, higher CO2 adsorption capacity, and increased photoactivities for photocatalytic CO2 reduction to CO and CH4 (71.52 μmol g −1  h −1 and 5.54 μmol g −1  h −1, respectively). As a comparison, the production rates of CO and CH4 are 29.36 μmol g −1  h −1 (CO) and 4.13 μmol g −1  h −1, respectively for pure LaFeO3 . The enhanced photoactivities are attributed to the increased electron‐hole separation rate resulting from the Er 3+ doping and improved CO2 adsorption capacity by MgO coupling. This work thus identifies a novel approach towards highly efficient photocatalysts for CO2 reduction. Abstract : Perovskite : Effective charge carrier separation and CO2 adsorption have been achieved by simultaneously Er 3+ ‐doping and MgO‐coupling in perovskite oxide photocatalyst, which resulted in a significant enhancement in photocatalytic CO2 reduction to CO and CH4 .